Pengaruh Konservatisme, Leverage, Profitabilitas, Ukuran Perusahaan Dan Kepemilikan Institusional Terhadap Tax Avoidance - Abdul Basir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Many companies consider paying taxes is unprofitable because it can reduce their amount of profit. This triggers companies are used various tactics to reduce the amount of tax payments. This study aims to analyze the factors influence of tax avoidance at Manufacturing Companies in the consumer goods sector in 2018-2022 period. These factors include accounting conservatism, DER, ROA, size firm and institutional ownership. The method of research is using the quantitative and regression analysis, the sample is Manufacturing Companies consumer goods sector which are consistently publish quarterly financial report period 2018-2022 with a total of 15 companies. Researcher collect the data by purposive sampling method, and it is analysed with EViews 10. Analysis was carried out by several tests such as classic assumption test, feasibility analysis model, panel regression analysis and coefficient of determination test. Based on research, tax avoidance of manufacturing companies is influenced by ROA and DER, while the accounting conservatism, size firm and institutional ownership does not have affect on tax avoidance of Manufacturing Companies consumer goods sector period 2018-2022. The company management is expected to pay more attention to every action taken and the risks it will bear in relation to its tax obligations. Keywords: Accounting Conservatism, DER, ROA, Size Firm, Institutional Ownership, Manufacturing Companies